First Report of the Anthracnose Pathogenic Agent on Walnut Fruits in China and Exploration of Its Biological Characteristics - Chen Zhou; Jinhuan Chen; Yonggang Liu; Ning Luo; Wei Guo; Mingming Shi; Huixia Li (Horticulturae)
Anthracnose is recognized as a significant agricultural disease. This study investigates the disease symptoms characterized by black dots on walnut fruits observed in the walnut orchards of Longnan City, Gansu Province, China, in June 2022. These symptoms resemble those of anthracnose reported in previous studies. A strain designated Ht-10 was initially isolated and identified as belonging to the Colletotrichum species based on its morphological features. Pathogenicity tests confirmed that this strain induced pronounced anthracnose symptoms in walnuts, consistent with those originally observed in the field. Subsequently, multilocus phylogenetic analysis, which included partial sequences of the internal transcribed spacer (ITS), actin (ACT), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), β-tubulin2 (TUB2), and chitin synthase (CHS-1) genes of Ht-10, indicated that it most likely clustered with Colletotrichum fioriniae. The determination of biological characteristics revealed that the optimal temperature for the growth of Ht-10 was 25 °C in full light at a pH of 6, with soluble starch and yeast paste serving as the optimal carbon and nitrogen sources, respectively. To our knowledge, this is the first report of C. fioriniae as a causal agent of anthracnose in walnut fruits in China.